THE IMPACT OF LEGISLATION ON ELECTORAL OPINION POLLS IN KENYA - Ndati, Ndeti; Wambua, Paul; Mogambi, Hezron (European Scientific Journal, ESJ, 2014)
This study sought to investigate the impact of legislation on electoral opinion polls in Kenya. It sought to determine the extent to which legislation influences voter’s access to credible, reliable and representative polls and the role of communication in creating awareness about electoral opinion polls.The study adopted descriptive survey design. Sampling was done through purposive and systematic random sampling techniques. Data was collected using a selfadministered questionnaire and also through Key Informant interviews. Quantitative data was analyzed using descriptive statistics while qualitative data was analyzed thematically. The study found out that legislation on electoral opinion polls influences electoral opinion polling in Kenya. It also found that the major political parties usually influence electoral opinion polls in Kenya; that legislation influences voter’s access to credible, reliable and representative polls; and that communication plays a very significant role in electoral opinion polls. The Paper recommends that the current legislation on electoral opinion polls should be evaluated to ensure objectivity and that citizen’s rights to access information should not compromised by law. At the same time, the relevant bodies should educate the public on the role and importance of polls.